Strategi Rekrutmen Kepemimpinan Perempuan Partai Keadilan Sejahtera (PKS) di Kota Pematang Siantar - Muhammad Ichsan; Junaidi Junaidi; Farhan Indra (Universitas Mataram, 2023)
This journal discusses the recruitment strategy of the Prosperous Justice Party in Pematang Siantar City for women's representation. This study aims to determine the strategy of recruitment and strategy of cultivating the leadership aspect of female cadre candidates for the Prosperous Justice Party (PKS) in Pematang Siantar City. This study uses a qualitative research type through descriptive analysis to describe the recruitment strategy carried out by the Prosperous Justice Party (PKS) in Pematang Siantar City in recruiting female cadre candidates. Data collection techniques used through interviews as primary data and literature study as secondary data. The results of this study indicate that the Prosperous Justice Party (PKS) in Pematang Siantar City is open in recruiting female cadre candidates using two recruitment strategies: First, the individual recruitment pattern is carried out using the person-to-person approach (al-da'wah al-fardiyyah). Second, the pattern of institutional recruitment which is carried out by affiliated methods with various party wing organizations with formal or informal status (al-da'wah al-jama'i).